Handling complaints [videorecording] - Educational Foundation (National Restaurant Association). (Chicago, Ill. Educational Foundation, National Restaurant Association, 1992)
Designed to help foodservice employees understand the importance of handling complaints, how to handle complaints, how to handle the irate customer, and how to prevent complaints
VC 1938
VHS format
Keywords: Table service; Food service employees -- Training of